Morphological Analysis of Brain Damage Due to Accident Injury Through Forensic Examination - Tuan Anh, Nguyen; Sy Hung, Luu; Dai Ha, Duong (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 37 No 1DO - 10.25073/2588-1132/vnumps.4293, 2021)
In forensic examination injury is a noun to refer to injury caused by external forces and reactions of the body. There are many causes of injury (self-generated accidents) such as traffic accidents, work accidents, domestic accidents, self-inflicted accidents…. The form of damage is heavy, light, shallow, and deep depending on the characteristics, weight, direction and force of the impacted object. In accidents, traumatic brain injury is a serious injury that has many consequences for the victim such as mental disorder, post-traumatic depression syndrome, post-traumatic brain disease, epilepsy, dementia… More severely, brain stamping can be fatal. The study was conducted from 01/01/2015 to 30/09/2019 We collected 98 cases of victims who died with brain damage. According to our research, brain stamping at the affected place accounted for the highest percentage (76.5%), followed by fracture of skull fracture (38.8%), opposing brain stamping on the opposite side (18.4 %), cerebral suppression due to hernia (10.2%), cerebral suppression due to sudden increase and decrease in speed (4.1%), intermediate cerebral suppression (3.1%). Combined intracranial lesions accounted for the majority (56.3%). Keywords Accident, Road trafic accident, head injurie, skull fracture, contre – coup fractures, forensic exam. References [1] Wikipedia Wikipedia The free encyclophedia. Cerebral contusion, accessed October 1, 2015, web https://en.wikipedia.org/wiki/Cerebral_contusion [2] N.N. Chung, Brain stamping, hematoma in the brain, Graduation thesis of Doctor CKI, Hanoi Medical University, accessed 15/8/2014(in Vietnamese). [3] Hideo Itabashi, John Andrews, Uwamie Tomiyasu, Stephanie Erlich, Lakshmanan Sathyavagiswaran, Forensic Neuropathology, Contusional brain injury and intracerebral haemorrhage, 2005. [4] Di Maio V,J, Di Maio D, Trauma to the skull and brain: crainiocerebral injuries, Forensic Pathology, Boca Raton, 2001. [5] National Accidental Injury Survey, Ministry of Health, 2010. [6] C.W. Runyan, Introduction: Back to the future – Revisitin Haddon's conceptualization of injury epidemiology and prevention, Epidemiology and Prevention 25(1) (2003) 60-64. https://doi.org/10.1093/epirev/mxg005. [7] Decision on the issuance of guidelines for building safe communities, prevention of accidents and injuries, Ministry of Health, 2006. [8] T.X. Ha, Morphology study of brain crushing injury caused by road traffic accident through forensic examination, Science Journal, Hanoi National University 33 (1) (2017) (in Vietnamese). [9] N.C. Cuong, Research on traumatic brain injury due to road traffic accident through forensic examination, Master's thesis, Hanoi Medical University, 2014 (in Vietnamese). [10] L.S. Hung, Research morphological characteristics of skull fracture caused by road traffic accident through forensic examination at Viet Duc Hospital, Scientific Journal of Hanoi National University, 33(1) ( 2017) 1-5 (in Vietnamese). [11] N.H. Long, D.G. Duc, Research on blood lcohol concentration and injury characteristics of road traffic deaths, Journal of Medical Research 74(3) (2011) (in Vietnamese). [12] B.R Sharma, Patterns of Fatal Head Injury in Road Traffic Accidents, Bahrain Medical Bulletin 25(1) (2003). [13] American Medical Forensic Specialists Inc Epidural hematoma, accessed October 1 (2015) http://www.baileylaw.com/docts/epidurahematoma.htm